Regulation of Synthesis of Methionyl-, Prolyl-, and Threonyl-Transfer Ribonucleic Acid Synthetases of Escherichia coli - Archibold, E. R. (1972)
Proline- and threonine-restricted growth caused a three- to fourfold derepression of the differential rate of synthesis of the prolyl- and threonyl-transfer ribonucleic acid (tRNA) synthetases, respectively. Similarly, there was approximately a 24-fold derepression in the rate of synthesis of methionyl-tRNA synthetase during methionine restriction. Addition of the respective amino acids to such derepressed cultures resulted in a repression of synthesis of their cognate synthetases. These results support previous findings and further strengthen the idea that the formation of aminoacyl-tRNA synthetases is regulated by some mechanism which is mediated by the cognate amino acids.